Behavioral Counseling Approach Modeling Techniques For Reducing Aggressive Behavior In Creating Child-Friendly Schools: Behavioral Counseling Approach Modeling Techniques For Reducing Aggressive Behavior In Creating Child-Friendly Schools - Muh Klasin; Ni Wayan Ari Farnili; Muhamad Saiful Umam (Universitas Pendidikan Ganesha, 2026)
This study aims to examine the effectiveness of the behavioral counseling approach with modeling techniques in reducing aggressive behavior among junior high school students and strengthening the eight dimensions of the Profil Pelajar Pancasila (Pancasila Student Profile) as stipulated in the Regulation of the Minister of Education, Culture, Research, and Technology (Permendikbudristek) Number 25 of 2024. The research employed a quantitative approach with a One Group Pretest–Posttest experimental design, involving 32 eighth-grade students of SMP Negeri 34 Semarang selected through random sampling using random classes as intact groups. The research instrument was an aggressive behavior scale consisting of 32 items, tested for validity and reliability (r₁₁ = 0.980). The analysis results showed a significant difference between pretest and posttest scores (tₒbₛ = 5.111 > tₜₐᵦ = 1.695; p < 0.05), indicating that the modeling technique was effective in reducing students’ aggressive behavior. Through observation, imitation, and positive reinforcement, students demonstrated improvements in self-control, empathy, responsibility, and assertive communication. Theoretically, the findings support Bandura’s social learning theory, while practically, they contribute to strengthening the dimensions of noble character, independence, critical reasoning, creativity, cooperation, and global diversity. Therefore, behavioral counseling with modeling techniques is feasible to be applied as a psycho-pedagogical intervention strategy to foster Pancasila-characterized students toward realizing Indonesia’s Golden Generation 2045.